Automatic data processing system for integrated cost and schedule control of excavation works in NATM tunnels - Cho, Daegu; Cho, Hunhee; Kim, Daewon (Journal of Civil Engineering and Management, 2014)
A type-based system is widely used for cost and schedule control in the NATM (New Austrian Tunnelling Method) tunnel. This study raises several limitations of the type-based system: a broad level of control, a distributed approach to cost and schedule data, ad hoc management, and difficulty in deriving meaningful data. Integrated cost and schedule control promises a myriad of benefits on both information flow and construction management. Nevertheless, the integrated approach still seems to be a long way from common use in the construction industry because it requires considerable overhead effort to acquire, track, and analyze the integrated data. The objective of this study is to propose a new method to automate the required processes for implementing cost and schedule integration. We propose an operational-level automatic data processing system for cost and schedule integration. The proposed system consists of a real-time location system for detecting equipment locations, a wireless mesh network for transmitting the location signals to a field office, and a prototype model for transforming the signals to cost and schedule data. Technical feasibility is analyzed through a pilot project. The study offers a new approach to facilitating sensor technologies for cost and schedule integration.